Navigating crisis: Graduate international students’ academic experiences and faculty support at HBCUs during COVID-19 - Brown-Grier, Ashleigh (Journal of International Students, 2026)
Graduate international students at Historically Black Colleges and Universities (HBCUs) faced significant inequities in their classroom experiences during COVID-19, a global crisis that exposed longstanding disparities in institutional preparedness and academic support. In this study, inequities are defined as barriers that limited students’ ability to fully engage in academic learning, including interruptions to instruction, reductions in access to technology and academic support, challenges related to language proficiency, and alterations in interactions with faculty. Using a hermeneutic phenomenological approach, this study examined the academic transitional experiences of 11 graduate international students enrolled at HBCUs during the pandemic. Guided by Schlossberg’s Transition Theory and its Four S’s framework, findings revealed challenges related to remote learning, diminished confidence in classroom participation, and perceived declines in English language proficiency. As global disruptions increasingly shape international student mobility and academic engagement, this study addresses a critical gap in the literature and underscores the need for equitable, crisis-responsive academic support structures for international students at HBCUs.